Pengaruh Pendidikan Perkoperasian terhadap Partisipasi Anggota Pada Koperasi Wanita di Kabupaten Tulungagung - Muhammad Anasrulloh; Adib Minanur Rokhim; Anna Febrian Firotul M (Fakultas Ekonomi Universitas Panca Marga, 2020)
Cooperatives aim to improve the welfare of members in particular and society in general, as well as participate in building the national economic order, to achieve this, of course, cooperatives must be independent and more developed with the support of active comprehensive participation from their members. Cooperatives are expected to be independent, resilient and efficient so that they will be able to face various economic problems. Cooperatives must be improved so that income distribution and poverty alleviation, especially for members, can be realized. Cooperatives require an active role of their members in all cooperative activities, this active role is created when there is a feeling of belonging so that they can effectively take part in cooperative decision making. However, a cooperative whose business is in the service sector is certainly not easy to invite participation in all aspects of activities, it requires an appropriate and appropriate strategy, one strategy that can be used to increase member participation is Cooperative Education. This study aims to determine how much influence Cooperative Education has on member participation in Women's Cooperatives (Kopwan) in Tulungagung Regency.